2022
DOI: 10.3389/fgene.2022.1038585
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals potential marker genes for diagnosis of Alzheimer’s disease and vascular dementia

Abstract: Alzheimer’s disease (AD) and vascular dementia (VD) are the two most common forms of dementia, share similar symptoms, and are sometimes difficult to distinguish. To investigate the potential mechanisms by which they differ, we identified differentially expressed genes in blood and brain samples from patients with these diseases, and performed weighted gene co-expression network analysis and other bioinformatics analyses. Weighted gene co-expression network analysis resulted in mining of different modules base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Another altered protein related to LTP maintenance is CaMKK2. This kinase is necessary for late-LTP, since it is involved in the synthesis of plasticity related proteins and the subsequent memory consolidation (Figure 6) [7983], and the overactivation of this pathway has been related to synaptic loss in a transgenic AD mice model [84, 85]. Interestingly, CaMKK2 has a male-specific role in hippocampal memory formation [86], thus the overexpression of CaMKK2 in male mice after oA β 1-42 injection might be contributing to LTP and memory deficits specifically in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another altered protein related to LTP maintenance is CaMKK2. This kinase is necessary for late-LTP, since it is involved in the synthesis of plasticity related proteins and the subsequent memory consolidation (Figure 6) [7983], and the overactivation of this pathway has been related to synaptic loss in a transgenic AD mice model [84, 85]. Interestingly, CaMKK2 has a male-specific role in hippocampal memory formation [86], thus the overexpression of CaMKK2 in male mice after oA β 1-42 injection might be contributing to LTP and memory deficits specifically in males.…”
Section: Discussionmentioning
confidence: 99%
“…Another altered protein related to LTP maintenance is CaMKK2. This kinase is necessary for late-LTP, since it is involved in the synthesis of plasticity related proteins and the subsequent memory consolidation (Figure 6) [79][80][81][82][83], and the overactivation of this pathway has been related to synaptic loss in a transgenic AD mice model [84,85].…”
Section: Sexual Dimorphism Differencesmentioning
confidence: 99%
“…P-type ATPases are essential ion-transporting pumps while V-type ATPase acidify different intracellular organelles and pump protons across the plasma membranes. ATP1A3 was previously identified as one potential marker for AD diagnosis compared with vascular dementia [ 40 ]. It encodes for Na + /K + -ATPase α3 subunit (NAKα3).…”
Section: Discussionmentioning
confidence: 99%
“…In comparing AD and VaD, one study has demonstrated differential patterns of CBF reduction in the frontal and parietal cortices [16], while another study has indicated reductions in the frontal and temporal regions [17]. Furthermore, recent years have seen a growing number of studies leveraging biological data, such as biomarkers and marker genes, to delve into the distinctions between AD and VaD [18][19][20]. This approach aids in enhancing our comprehension of disease pathways and mechanisms, and serves to validate prevailing hypotheses.…”
Section: Introductionmentioning
confidence: 99%